Handbook of shale gas law and policy : economics, access, law and regulation in key jurisdictions / edited by Tina Hunter. - Tina, Hunter (Energy & law, 2016)
To date, petroleum law and policy in Europe has focused offshore. Over the last fifty years it has been driven by the development and regulation of vast oil and gas resources in the North Sea. However, a new source of petroleum is now emerging in Europe - that of the unconventional resource of shale gas. Since 2011, the UK has been striving to undertake the development of shale gas through the granting of a consent to drill. Concentrating solely on shale gas, this book is structured around five themes, namely an overview and introduction to shale gas activities, shale gas economics and energy security, access to shale gas resources, shale gas law and regulation, and the future of shale gas. It examines the fundamental principles and provides the reader with a practical, applicable analysis of shale gas exploration and extraction. Looking at the legal, scientific and economic issues relating to shale gas extraction from the perspective of developed (United States and Canada), developing (Australia) and emerging jurisdictions (United Kingdom), this book provides unique perspectives that the reader can apply to their own jurisdiction. With contributions by Roberto F. Aguilera, David Campin, Simone Fraser, Andrew Garnett, Tina Hunter, Allan Ingelson, Andrey Konoplyanik, Steven Latta, Alastair R. Lucas, Cristelle Maurin, David M. Ong, John Paterson, Marian Radetzki, Slawomir Raszewski, Peter Styles, Emre & Úsenmez, Vlado Vivoda, Michael Weir and Hannah J. Wiseman. Dr Tina Hunter is a Professor in Energy Law and the Director of the Centre for Energy Law, University of Aberdeen, United Kingdom.